2015
DOI: 10.17795/zjrms1007
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Overview of the Effects of Melissa officinalis L. Extract on the Function of Various Body Organs

Abstract: Melissa officinalis (lemon balm) which belongs to the Lamiaceae family is a known herb that has long been used in traditional medicine to treat many disorders, and several studies have been conducted to identify the plant and its healing properties. The purpose of this article is to review a series of studies on the effects of the herb extract on the function of various body organs. Due to its volatile organic compounds and active constituents such as terpenoids, flavonoids, quercetin, rutin, quercitrin, galli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 28 publications
(32 reference statements)
2
40
0
1
Order By: Relevance
“…M. officinalis has a large use in traditional medicine, food industry, and aromatherapy, due to its fresh smell and its medicinal properties including hypoglycemic, hepatoprotective, antimicrobial, antidepressant, hypnotic, and sedative [ 1 , 11 14 ]. In addition, there are studies that pointed out the cytotoxic effect of lemon balm extract on breast cancer [ 13 ] and colon carcinoma [ 15 ]. Chemical composition of lemon balm is diverse and includes phenolic acids, tannins, flavonoids, terpenes (triterpenes, monoterpenes, and sesquiterpenes), and volatile compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…M. officinalis has a large use in traditional medicine, food industry, and aromatherapy, due to its fresh smell and its medicinal properties including hypoglycemic, hepatoprotective, antimicrobial, antidepressant, hypnotic, and sedative [ 1 , 11 14 ]. In addition, there are studies that pointed out the cytotoxic effect of lemon balm extract on breast cancer [ 13 ] and colon carcinoma [ 15 ]. Chemical composition of lemon balm is diverse and includes phenolic acids, tannins, flavonoids, terpenes (triterpenes, monoterpenes, and sesquiterpenes), and volatile compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Not only does lemon balm have an impressive background from traditional medicine, but, according to the latest studies, it is effective in cardiovascular disease, by decreasing the values of total lipid concentration, improving HDL (high density lipoprotein) values, and lowering the hepatic synthesis of cholesterol [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lemon balm is a natural source of rosmarinic acid (RA). RA is one of the main phenolic acids in the chemical composition of Melissa officinalis L., and it determines the pharmacological effect and the medical use of the plant [ 2 5 ]. Current studies have shown that lemon balm preparations have bacteriostatic, antimicrobial, and antiviral effects [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the methanolic leaf extract of Securinega virosa demonstrated related antinociceptive effect in acetic acid induced writhing test and formalin test models [33]. That the aqueous extracts of A. nilotica produced non-dose dependent analgesic activity is related to studies by Zarei et al [34] who observed the antinociceptive activities of Melissa officinalis leaf extracts in laboratory animals. The dose ranges used in this study were within the dose ranges used by Ishola et al [35][36][37].…”
Section: Animal Modelsmentioning
confidence: 92%